Scientific generalizing of modern approaches to routine immunization over the world - А. А. Kotvitska; O. V. Kononenko; I. V. Kubareva (Zaporozhye State Medical University, 2014)
Aim. The experience of the routine population vaccination in 53 countries of Europe, including Ukraine has been generalized in the article. Methods and results. The main legislative bases of vaccination in these countries according to the national calendars of preventive vaccination have been determined. The similarities between foreign and national system of routine population vaccination have been defined. It has been established that in most European countries, the calendar of preventive vaccinations has recommending character. Studied countries have been systematized due to the presence of infectious diseases in the national calendars of preventive vaccinations and also a number of infectious nosologies present in the calendars of all the studied countries have been distinguished. Conclusion. Basic measures to improve routine vaccination of national population have been substantiated.